Identification and expression of gonadotrophin hormones in gouramy (Osphronemous gouramy, Lacepède, 1801) under photoperiod manipulations - norman prayogo; asrul siregar; purnama sukardi; yasumasa bessho (Society for Indonesian Biodiversity, 2020)
Abstract. Prayogo NA, Siregar AS, Sukardi P, Bessho Y. 2020. Identification and expression of gonadotrophin hormones in gouramy (Osphronemoous gouramy, Lacepède, 1801) under photoperiod manipulations. Biodiversitas 21: 1365-1372. The environment influences fish reproduction. One of the influential environmental factors is photoperiod that regulates the production of hormones for gonad growth and development, gametogenesis, then the reproductive cycle. This research was conducted to determine the effect of photoperiod on the reproductive performance of gouramy with different photoperiod treatments. The design of this study was four photoperiod treatments consisting of 14L: 10D, 16L: 8D and 18L: 6D and controls. Fish samples were divided into 4 aquariums consisting of nine fish and repetition was conducted on each. Fish were kept under photoperiod treatment for 16 weeks. The observed variable was pituitary activity. Pituitary activity was evaluated by measuring the expression of FSH and LH genes using Real Time PCR. The results showed that gouramy had FSH and LH genes with 483 bp and 506 bp. FSH and LH gene expression increased with long photoperiod exposure (P <0.05). These findings indicate that photoperiods regulate the reproduction of gouramy through the HPG axis and control the production of the hormone Gonadotropin.